Risk-Averse Optimal Bidding Strategy for Wind Energy Portfolio Manager - Cicek, Alper; Erdinc, Ozan (IEEE, 2020)
Since conventional sources pollute the environment due to the carbon emissions and it is estimated that these will be depleted in the near future, states have turned to renewable energy. The number of renewables is increasing with the help of various support policies. Wind energy constitute a significant part of this increase. Besides, in many countries, it mandatories for these sources to participate in electricity markets. These stochastic sources may experience imbalances in real-time power delivery. In this respect, it seems reasonable that wind energy sources should be gathered under portfolio manager so that eliminate imbalances. In this study. a structure is proposed that the wind energy portfolio manager aims to maximize total profit by participating in the day-ahead and balancing market, considering the risk. To prove effectiviness of the proposed structure, several case studies were carried out with Turkey and Sweden electricity market prices.
Keywords: Engineering